From the outside in: tutor perspectives of student transformative experiences within Indigenous Studies health education. Issue 3 (16th April 2019) - Bullen, Jonathan; Roberts, Lynne
ABSTRACT: While more is becoming understood about the effects of Indigenous Studies health curricula on student preparedness and attitudes toward working in Indigenous health contexts, less is known about how tutors in this space interpret student experiences and contribute to the development of preparedness. Reporting on a qualitative study, this article provides insight into tutors' perceptions of tertiary first year health students' transformative experiences in an Indigenous Studies health course. Twelve Indigenous and non-Indigenous tutors were interviewed about their teaching experiences within this context. Framed by Mezirow's transformative learning theory, thematic analysis findings suggest tutors observe several precursor steps to transformative learning including disorienting dilemmas, critical reflection on assumptions, exploration of new roles, and trying on new roles. The content of these themes extends our understanding of how these precursor steps manifest, and the elements related to this. Findings also suggest tutors vary in their identification, interpretation and response to many of these pedagogical entry points. Within this learning context, the concept of teacher/student relationship is suggested as playing a meaningful role in the positioning and efficacy of tutors. This impacts tutors' understanding of transformative learning, the social construction of students, consequent interpretations of student experiences, and means of facilitating cognitive and affective learning. We propose a reconceptualisation of thinking around teaching in this space, with a focus on both further development of educator capabilities and student curricular opportunities to promote transformative learning appropriate to the stated goals of the Australian Indigenous Studies learning and teaching context. The findings indicate that institutional investment in the development of educators in this space remains vitally important.